Integrated Analysis of Key Genes and Pathways Involved in Fetal Growth Restriction and Their Associations With the Dysregulation of the Maternal Immune System - Wang, Xue; Zhu, Hong; Lei, Lei; Zhang, Yang; Tang, Chao; Wu, Jia-xing; Zhou, Jie-ru; Xiao, Xi-rong (Frontiers in Genetics, 2021)
Fetal growth restriction (FGR) is a common pregnancy complication and a risk factor for infant death. Most patients with FGR have preeclampsia, gestational diabetes mellitus, or other etiologies, making it difficult to determine the specific molecular mechanisms underlying FGR. In this study, an integrated analysis was performed using gene expression profiles obtained from Gene Expression Omnibus. Differentially expressed genes (DEGs) between healthy and FGR groups were screened and evaluated by functional enrichment and network analyses. In total, 80 common DEGs (FDR < 0.05) and 17 significant DEGs (FDR < 0.005) were screened. These genes were enriched for functions in immune system dysregulation in the placenta based on Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses. Among hub genes identified as candidates for FGR and fetal reprogramming, LEP, GBP5, HLA–DQA1, and CTGF were checked by quantitative polymerase chain reaction, immunohistochemistry, and western blot assays in placental tissues. Immune imbalance could cause hypoxia environment in placenta tissues, thus regulating the fetal-reprogramming. A significant association between CTGF and HIF-1α levels was confirmed in placenta tissues and HTR8 cells under hypoxia. Our results suggest that an immune imbalance in the placenta causes FGR without other complications. We provide the first evidence for roles of CTGF in FGR and show that CTGF may function via HIF-1α-related pathways. Our findings elucidate the pathogenesis of FGR and provide new therapeutic targets.